2010
DOI: 10.5051/jpis.2010.40.4.180
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous healing capacity of rabbit cranial defects of various sizes

Abstract: PurposeThis study evaluated the spontaneous healing capacity of surgically produced cranial defects in rabbits with different healing periods in order to determine the critical size defect (CSD) of the rabbit cranium.MethodsThirty-two New Zealand white rabbits were used in this study. Defects of three sizes (6, 8, and 11 mm) were created in each of 16 randomly selected rabbits, and 15-mm defects were created individually in another 16 rabbits. The defects were analyzed using radiography, histologic analysis, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
118
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 120 publications
(123 citation statements)
references
References 26 publications
4
118
1
Order By: Relevance
“…16,17 In previous study using surgically created circular defects of 6, 8, 11, and 15 mm in the craniums of rabbits, the healing capacity from the defect margin was reported to be constant at the same healing period regardless of the defect size. 18 Furthermore, many researchers have selected a defect smaller than the critical sized defect for investigating the early events of regeneration. 19,20 Therefore, we selected the 6 mm defect to investigate the additional effects of PRP and MSC on bone healing capacity during relatively short-term period.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 In previous study using surgically created circular defects of 6, 8, 11, and 15 mm in the craniums of rabbits, the healing capacity from the defect margin was reported to be constant at the same healing period regardless of the defect size. 18 Furthermore, many researchers have selected a defect smaller than the critical sized defect for investigating the early events of regeneration. 19,20 Therefore, we selected the 6 mm defect to investigate the additional effects of PRP and MSC on bone healing capacity during relatively short-term period.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we evaluated the outcome of these graft materials at 4 weeks postoperatively, which represents the early phase of the healing response, and measured properties such as the stability of the materials and host reactions; at 8 weeks postoperatively, which represents the late healing response, we measured processes such as bone incorporation, resorption of materials, bone remodeling, and the amount of bone regeneration [22]. …”
Section: Discussionmentioning
confidence: 99%
“…In this study, the bone defects were smaller than the Critical Size Defect (CSD) in rabbits. CSD is known as the smallest defect on a bone of specific species which will not spontaneously repair during its life time [21]. Although a range of 10-15 mm has been considered as the critical size defect of rabbits' calvaria, some studies have concluded that it is not possible to define the exact dimension of CSD [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…CSD is known as the smallest defect on a bone of specific species which will not spontaneously repair during its life time [21]. Although a range of 10-15 mm has been considered as the critical size defect of rabbits' calvaria, some studies have concluded that it is not possible to define the exact dimension of CSD [21,22]. Furthermore, it has been suggested that the term ''critical size defect" should no longer be used because the repair potential of bony margin was shown to be constant despite defect size [22].…”
Section: Discussionmentioning
confidence: 99%